KESANTUNAN BERBAHASA INDONESIA DALAM BERKOMUNIKASI DOSEN DAN MAHASISWA IAIN RADEN INTAN LAMPUNG - MARDIYAH, MARDIYAH (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2016)
The ethically communication activity is needed by the students of Indonesian Education and Art Department while interacting with the staffs since the area of campus is the educational area, so the students have toshow their respectful to the staffs by using well mannered languages.This research formulates the problem into two, they are (1) How is the ethical communication used by the students of FDIK  academic year 2011- 2013 with the staffs of FDIK in form of languages. (2) How is the principles fault of ethical communication used by the students of FDIK academic year 2008-2011 with the staf in form of languages.Based on the aboveformulation, the objectives of this research are (1) to describe the ethical languages used by the students of FDIK academic year 2011-2013 with the staffs in form of languages.(2) To describe the principles fault of ethical communication used by the students of FDIK academic year 2011-2013 with the staffs in form of languages.This study ses Ethical Principles by Leech. This research uses qualitative-descriptive method. Tabulation of data result shows that (1)Ethical language which often used by the students in communication with the staffs is tact maxim, generosity maxim, approbation maxim, Aggrement maxim, sympathy maxim. (2) Unethicallanguage that often appear is a language that break tact maxim and approbation maxim principles